1982
DOI: 10.1177/30.1.7054274
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum phosphate visualisation of acid phosphatase activity: a biochemical and x-ray microanalysis study.

Abstract: A new method is described that demonstrates acid phosphatase activity in the cells of the proximal tubules of the rat kidney. The method is based on the formation of an insoluble aluminum phosphate precipitate. Microanalysis was used to demonstrate the presence of intracellular aluminum and determine the quantity present under the probe. Parallel biochemical studies showed that the aluminum precipitate was indeed due to acid phosphatase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…In the lysosomes, Cr was concentrated in an insoluble from and associated wi.th phosphorus and sulfur. Chromium phosphate was the result of a n enzymatic reaction of acid phosphatase activity, as previously demonstrated by a method based on its microanalytical visualisation (Berry et al 1982). The presence of sulfur, associated with Cr in the lysosome, may b e explained by the possible existence of thionein-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the lysosomes, Cr was concentrated in an insoluble from and associated wi.th phosphorus and sulfur. Chromium phosphate was the result of a n enzymatic reaction of acid phosphatase activity, as previously demonstrated by a method based on its microanalytical visualisation (Berry et al 1982). The presence of sulfur, associated with Cr in the lysosome, may b e explained by the possible existence of thionein-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms have been proposed and studied in vivo for selective concentration of elements present in minerals as insoluble phosphate salts (18,19,24), and more recently, Galle tron microscopy and microanalysis the composition and morphology of dense phosphate deposits inside rat macrophages after inhalation of mineral salt-based aerosols (20). These precipitates exhibit granular morphologies not unlike those of the silica precipitates observed in the present experiments.…”
Section: Discussionmentioning
confidence: 55%
“…One proposed mechanism is that the dust particles cause the macrophage to generate enzymes that eventually lead to its destruction and the formation of abnormal tissue in the lung (16,17). Although one of the normal mechanisms for the elimination of foreign particles relies on the capability of macrophages to dissolve solid particles of low aqueous solubility (18)(19)(20), recent studies have shown that the opposite can also occur [i.e., that the lysosome of lung macrophages may concentrate and precipitate elements inhaled as a part of water soluble compounds (21)]. …”
mentioning
confidence: 99%
“…The proposed mechanism to explain the concentration precipitation phenomenon is an in vitro Gomori reaction related with the high intralysosomal phosphatase activity (Berry et al, 1982).…”
Section: Discussionmentioning
confidence: 99%